Effects of Self-efficacy and Wisdom on Job Competence of Care Workers in Korea (Medico Legal Update, 2020)
Purpose: The purpose of this study was to analyze the effect that self-efficacy and wisdom on job competencein care worker in Korea.Method: The subjects of this study were 123 care workers. The data were analyzed using descriptivestatistics, t-test, ANOVA, Pearson’s correlation coefficient and stepwise multiple regression using the SPSSWindow 23.0 program.Results: The care workers’ self-efficacy scored 3.80 points out of 5 points and wisdom scored 3.63 pointsout of 5 points and job competence scored 3.66 points out of 5 points. The job competence of care workerswas a high positive correlation with self-efficacy (r=.53, p